Pemanfaatan ampas batang kelapa sawit tua bebas nira sebagai bahan baku biopelet [Utilization of sap free old palm dregs as raw material for biopellets] - Utomo, Tanto Pratondo; Hasanudin, Udin; Hidayati, Sri; Widaputri, Silaturahmi (Jurnal Teknologi & Industri Hasil Pertanian, 2024)
Palm oil plants, after reaching the end of their productive life, need to be rejuvenated with proper handling to prevent old palm trunks, which have been cut down, from being infested by beetles and the growth of Ganoderma sp. fungus, which can damage productive palm oil plants in the vicinity. The old oil palm trunks contain sap and have been utilized. The residue of the oil palm trunk after sap extraction contains carbon compounds that can be used as raw material for bio-pellets, representing an added value potential.  In this study, the composition of sap-free palm trunk dregs as raw material for bio pellets and the manufacture of bio pellets using sap-free palm dregs with a combination of particle size treatment and pressing pressure of T1M1 (0.4882 kg/cm2; 10 mesh); T1M2 (0.4882 kg/cm2; 20 mesh); T1M3 (0.4882 kg/cm2; 40 mesh); T2M1 (0.9764 kg/cm2; 10 mesh); T2M2 (0.9764 kg/cm2; 20 mesh); T2M3 (0.9764 kg/cm2; 40 mesh); T3M1 (1.4647 kg/cm2; 10 mesh); T3M2 (1.4647 kg/cm2; 20 mesh); and T3M3 (1.4647 kg/cm2; 40 mesh) using a hydraulic shop press to produce bio-pellets with a length of 2.5 cm and a diameter of 1.2 cm. The research used a descriptive method by presenting data as diagrams and tables. The results showed that the nira-free palm dregs used as raw material for the best bio-pellets in the T2M1 treatment (0.9764 kg/cm2; 10 mesh) contained 25.7% hemicellulose, 47.6% cellulose, and 7.2% lignin. The pellets produced contained 6.50% moisture content, 5.01% ash content, and 4416.93 cal/g heating value.